Intelligent Detection and Localization of Cable Faults Using Advanced Discharge Analysis Techniques (Informatica, 2025)
Aim: This article proposes a method based on oscillation wave partial discharge detection for locating power cable faults, with the aim of quickly identifying the insulation aging status and faults in power cables. Methodology: This method introduces the principles and experimental devices used in oscillation wave partial discharge experiments. It also compares and analyzes three power cables with significant differences in insulation aging levels and insulation defects at cable joints and terminals. We established the relationship between the degree of insulation aging and the partial discharge parameters of the cable, including discharge starting voltage and discharge quantity. We applied the partial discharge localization method to analyze the location of cable insulation aging faults. Results: The experiments demonstrated that, in comparison to cables A and C, the insulation strength of cable B was significantly worse, even exceeding three orders of magnitude. Conclusion: The tan δ value for each phase of Cable B was two to three orders of magnitude larger than that of Cable A and Cable C. Both experimental results were in agreement, highlighting the effectiveness and applicability of the partial discharge experiment with damping oscillating wave voltage.